2008
DOI: 10.1007/s10804-008-9047-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Caregiving: Perceived Parental Relations and Current Social Support

Abstract: There is very little research on the effects of early caregiving on adult development. The purpose of the present study was to: (1) provide descriptive information on young caregivers, and (2) determine if there is a relation between early caregiving experiences, early parent-child relations and their current (adult) social support. Early caregiving was defined as providing assistance with basic and/or instrumental activities of daily living to parents or adult relatives, while under the age of 21. Thirty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Pakenham et al (2006) found that child caregivers report more isolation than children with healthy parents due to their caregiving experiences. Shifren (2008) found that longer duration and higher frequency of early caregiving experiences were associated with less current affectionate support from others once former caregivers reached adulthood. Each of these studies provides an important contribution to understanding the former young caregivers' experiences.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Pakenham et al (2006) found that child caregivers report more isolation than children with healthy parents due to their caregiving experiences. Shifren (2008) found that longer duration and higher frequency of early caregiving experiences were associated with less current affectionate support from others once former caregivers reached adulthood. Each of these studies provides an important contribution to understanding the former young caregivers' experiences.…”
Section: Introductionmentioning
confidence: 92%
“…Becoming a caregiver can occur at any time in one's lifespan from childhood through older adulthood (Dellmann-Jenkins and Brittain 2003;Gates and Lackey 1998;Shifren 2008;Siskowski 2006;Stein et al 1998;Vitaliano et al 2003). US surveys on younger caregivers report that 1.3-1.4 million individuals between ages 8 and 18 years old may be young caregivers , and about 3.6-5.5 million individuals in emerging adulthood (18-25 years old) provide care for others .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations